The effect of teaching style and motivation on student football passing learning outcomes - AR, Sahabul Adri; Samsudin, Samsudin; Humaid, Hidayat (Edelweiss Applied Science and Technology, 2024)
This study aims to determine the effect of teaching style and learning motivation in football courses for students. This research is an experimental study using ANOVA analysis of variance with a quantitative approach. The results showed that there were significant changes from the pre-test and post-test results of several styles in learning by involving 220 respondents with an increase; training style 14.4, reciprocal style 9.87 and inclusion style 9.72 and learning motivation. Motivation is an important mediator in the relationship between variables.